Factors That Related To Cancer Related Fatigue - Nugroho, Santoso Tri (University of Muhammadiyah Semarang, 2019)
About 40% to 100% of cancer patients complaint of fatigue. Cancer Related Fatigue is the most disturbing symptom compared to another symptom, like nausea and vomiting. Persistent cancer-related fatigue can impact on patient quality of life because the patient becoming too tired to involve in the activity. Need study to recognize factors that related to fatigue so that as a nurse we can choose accurate nursing intervention to overcome cancer-related fatigue. Objective: To identify factors related to cancer-related fatigue. Methods: Literature were searched via Google scholar and Google search with keyword: fatigue, cancer, and nursing. Literature were in full text and published by the year 1999-2016. Literature that was in inclusion criteria than be analyzed. Result: From 6 kinds of literature that were analyzed we found out factors that are related to cancer-related fatigue. That is characteristic (age, sex), sociodemography (economic status), stadium cancer, exercise, pain, depression, and sleep quality. But the factor that most related to cancer-related fatigue remains unclear. Conclusion: Age, sex, economic status, stadium, exercise, pain, depression and sleep quality are factors that can be used as predictor fatigue.